The Contribution of Cooperatives and Micro, Small, and Medium Enterprises (MSMEs) to Community Welfare in Jambi City, 2020–2025 - Yudha Saputra; Dhefarell Jalingga; Dicky Setiawan; Aminah Ramalia (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This research looks at how cooperatives and small businesses in Jambi City have helped improve the well-being of the community between the years 2020 and 2025. This study looks at how poverty and economic inequality continue to exist even though the country's economy has been growing in a positive way. The research method used is a qualitative descriptive approach, which focuses on understanding a phenomenon thoroughly by closely examining the actual situation. Studies show that cooperatives and small and medium-sized businesses help improve the well-being of communities by providing jobs, boosting income, and supporting the local economy. However, this contribution hasn't reached its fullest potential because of some challenges, like not having enough money to invest, not having skilled enough workers, not having good access to markets, and not using digital tools properly. This means that even though there are some improvements in community well-being, these benefits are not shared equally, and there are still big differences in wealth and income between different areas. So, to make cooperatives and small businesses play a bigger role in helping the community in a lasting way, it's important to strengthen institutions, train the workforce, and speed up the digital transformation process.